Retracted: Ethno-pedagogy Perspective on Ethnic Minority Discourse of Education - Sulistyani, Hapsari Dwiningtyas; Rahardjo, Turnomo; Suprihatini, Taufik; Rahmiaji, Lintang Ratri (UI Scholars Hub, 2020)
This article has been retracted as it contained duplicate material that was originally published in Advances in Social Science, Education and Humanities Research, volume 214, 2nd International Conference on Educational Science (ICES 2018), pp. 223-230. The Editorial Board understands that this misconduct may have been unintentional. The authors provided us a clarification letter stating that they have not received confirmation regarding the publication of their article in the proceeding, and this was the basis of the authors’ submission to the Jurnal Komunikasi Indonesia. However, as an accredited journal under the Ministry of Education and Culture, we are obliged to follow the existing protocols and have decided to retract this article. The document and its content have been removed from Jurnal Komunikasi Indonesia, and reasonable effort should be made to remove all references to this article.